EFFECT OF DEEP TRAPS ON HOLE PHOTOCURRENT SOLAR CELLS BASED ON HYDROGENATED AMORPHOUS SILICON (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The use of amorphous hydrogenated silicon H Si a : − to create barrier devices for microelectronics seems to be of many savers, especially in the manufacture of photovoltaic cells.